Preface to “A discrete-time interpretation of the Planck-Einstein equation” - Vladimir Gontar (Discrete Dynamics in Nature and Society)
The article titled “A discrete-time interpretation of the Planck-Einstein equation” by A. Boyarsky intends to stimulate open discussions about the physical meaning of discretetime space dynamics. All your comments on this article are most welcome.